Sistem Informasi Geografis Sebaran Stunting Dan Tingkat Kemiskinan Di Provinsi Jawa Tengah Tahun 2023 - Aldi Widodo; Bambang Agus Herlambang (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the distribution of stunting and poverty levels in Central Java Province. This spatial analysis method allows researchers to understand the distribution of stunting and poverty levels, as well as the factors that influence their distribution. This study involves collecting spatial and non-spatial data, which is then analyzed spatially with a Geographic Information System. The results of the analysis provide in-depth insight into the research revealing the complex relationship between poverty and stunting in Central Java. The 2023 stunting distribution project tries to address multiple impacts through an integrated approach. The main challenges involve unequal income distribution and unequal access to education and employment. The need for a holistic strategy and continuous evaluation to achieve significant change.